2014
DOI: 10.1249/jsr.0000000000000085
|View full text |Cite
|
Sign up to set email alerts
|

Update

Abstract: Soccer, or football, as it is known in much of the world, is one of the most popular sports in the world. The purpose of this article was to provide a concise update on select soccer-specific medical issues published in the last year as they relate to soccer injury and prevention, concussions, and chronic groin pain. Both the Fédération Internationale de Football Association and the Union of European Football Associations published data from their longstanding injury tracking systems, providing foundation for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…There have been consistent efforts in recent years to determine the causality of a variety of types of football injuries and establish how to deal with them effectively. Readers are directed to relevant papers that discuss diverse traumatic injuries and less common injuries sustained in the competitive environment by both male and female athletes [ 41 44 ]. The present study has identified the potential importance of resilience as an important element within the context of injuries in football.…”
Section: Discussionmentioning
confidence: 99%
“…There have been consistent efforts in recent years to determine the causality of a variety of types of football injuries and establish how to deal with them effectively. Readers are directed to relevant papers that discuss diverse traumatic injuries and less common injuries sustained in the competitive environment by both male and female athletes [ 41 44 ]. The present study has identified the potential importance of resilience as an important element within the context of injuries in football.…”
Section: Discussionmentioning
confidence: 99%
“…With the FIFA 11+, a very successful warm‐up program has been created, which has been proven to reduce the risk of injuries of the lower extremity. Now, there is a need to include heading exercises to this program (Jones, 2014). It is also important that players as well as backyard personnel know more about the symptoms and possible consequences of a concussion or head injury.…”
Section: Discussionmentioning
confidence: 99%
“…The other is the Union of European Football Associations' (UEFA) Champions League Injury Study, (commonly UEFA injury study) that began in 2001 and has involved between 27 and 33 European soccer teams from 10 different countries for a period of 11 seasons. 10 Data from these surveillance systems showed that football injuries vary widely but many authors agree that the majority of injuries affect the lower extremities (60-90%), including the upper leg, knee and ankle, with lower frequencies for the head and neck (15%), trunk (8%) and upper extremities (7%). 8 9 20 21 The most commonly diagnosed injuries are contusions (55%), sprains (15%) and strains (10%), and most (80%) occur from contact with another player; 45-50% of contact injuries result from foul play.…”
Section: Introductionmentioning
confidence: 99%